Unusual ultra-hydrophilic, porous carbon cuboids for atmospheric-water capture - Hao, Guang-Ping; Mondin, Giovanni; Zheng, Zhikun; Biemelt, Tim; Klosz, Stefan; Schubel, Rene; Eychmueller, Alexander; Kaskel, Stefan (Angewandte Chemie International Edition, 2015)
There is significant interest in high-performance materials that can directly and efficiently capture water vapor, particularly from air. Herein, we report a class of novel porous carbon cuboids with unusual ultra-hydrophilic properties, over which the synergistic effects between surface heterogeneity and micropore architecture is maximized, leading to the best atmospheric water-capture performance among porous carbons to date, with a water capacity of up to 9.82 mmolg-1 at P/ P0= 0.2 and 25°C (20% relative humidity or 6000 ppm). Benefiting from properties, such as defined morphology, narrow pore size distribution, and high heterogeneity, this series of functional carbons may serve as model materials for fundamental research on carbon chemistry and the advance of new types of materials for water-vapor capture as well as other applications requiring combined highly hydrophilic surface chemistry, developed hierarchical porosity, and excellent stability.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carbon; Doping; Microporous materials; Nitrogen; Water-vapor capture